(3GdHMK GdYdej GdELJeGYj (B:s (3dZJg heOGNdg, efGgLg hWQGFbg (B/s - (3LdHj, Ydj YHO GdQGRbs; (3GdSjO, GdSjO YHO GdYGWj hBNQhfs ((3GdEScfOQjI(B: s (3OGQ GdeYQaI GdLGeYjI(B, s, 2003)
(3dZI GdHMK GdYdej GdELJeGYj hechfGJ GdfXQjI GdYdejI(B- (3CfhGY GdeYQaI hbhGYOgG(B- (3GSJNOGe GdefgL GdYdej(B( (3GdfTCI hGdJWhQ(B)- (3eOGNd OQGSI GdeLJeY(B- (3efGgL GdHMK GdYdej GdELJeGYj(B- (3WQb OQGSI GdeLJeY(B- (3COhGJ LeY GdHjGfGJ(B- (3YjfI GdHMK GdELJeGYj(B.s
(3GdeQGLY U(B.378s
Keywords: (3GdHMK GdELJeGYjs; (3GdHMK GdYdejs; (3Yde GdELJeGY(B- (3efGgL GdHMKs